Video Enhancement and Dynamic Range Control of HDR Sequences for Automotive Applications. (27th June 2007) - Marsi Marsi, Stefano Stefano; Impoco Impoco, Gaetano Gaetano; Ukovich Ukovich, Anna Anna; Carrato Carrato, Sergio Sergio; Ramponi Ramponi, Giovanni Giovanni
Abstract : CMOS video cameras with high dynamic range (HDR) output are particularly suitable for driving assistance applications, where lighting conditions can strongly vary, going from direct sunlight to dark areas in tunnels. However, common visualization devices can only handle a low dynamic range, and thus a dynamic range reduction is needed. Many algorithms have been proposed in the literature to reduce the dynamic range of still pictures. Anyway, extending the available methods to video is not straightforward, due to the peculiar nature of video data. We propose an algorithm for both reducing the dynamic range of video sequences and enhancing its appearance, thus improving visual quality and reducing temporal artifacts. We also provide an optimized version of our algorithm for a viable hardware implementation on an FPGA. The feasibility of this implementation is demonstrated by means of a case study.